PENERAPAN MODUL EKOSISTEM BERBASIS KONSTRUKTIVISME DI SMP YPE SEMARANG - Fitriani, Dwi; Endang Susilowati, Sri Mulyani; Priyono, Bambang (Journal of Biology Education, 2013)
One factorthat cansupport thesuccess ofthe learning processis the selection ofteaching materialswithappropriate learningmethod. Teaching materialsin learningmust beadapted tocharacteristics of students, basic competencies, andindicators ofachievementareexpected afterthe learning process. The results ofresearchers interviewswithBiology teacherandsome students, it was concluded that themain problems facedin learningbiology is thelack of duelearningsupport facilitiesthathandlestudentteaching materials. This research aims to testthe effectiveness of the modules implemented ecosystem-based constructivist learning in junior YPE Semarang. The population inthis research were allstudents of classVIIconsists oftwoclasses.This research was conductedwith the designcontrol grouppretest-posttest. Based on the resultsof t-testonstudent learning outcomesacquiredthitung>ttablethenH0is rejectedandH1accepted,so itwas concluded thatthe results ofstudyingthe experimental groupis higherthan theresults ofstudyingthe control group withthe percentage ofmastery learningclassicalexperimental groupreached 90% while the control groupat 50%. The results ofthe analysis ofthe teacherand thestudents to themodulereachesa percentage of100%with avery goodcriteriaindicatesthat themoduleis appliedtoattract studentstostudy the materialecosystem. Based on these resultsit can be concludedthat theEcosystem-Based ModuleConstructivismappliedeffectively usedasteaching materialin juniorYPESemarang.Â Penelitian ini bertujuan untuk menguji keefektifan modul ekosistem berbasis konstruktivisme yang diterapkan dalam pembelajaran di SMP YPE Semarang. Populasi dalam penelitian ini adalah seluruh siswa kelas VII yang terdiri dari dua kelas. Penelitian ini dilakukan dengan desain control group pre test-post test. Berdasarkan hasil uji t terhadap hasil belajar siswa diperoleh thitung>ttabel maka H0 ditolak dan H1 diterima, sehingga disimpulkan bahwa hasil belajar kelompok eksperimen lebih tinggi dibandingkan dengan hasil belajar kelompok kontrol dengan presentase ketuntasan belajar klasikal kelompok eksperimen mencapai 90% sedangkan kelompok kontrol hanya mencapai 50%. Hasil analisis tanggapan guru dan siswa terhadap modul mencapai presentase 100% dengan kriteria sangat baik menunjukkan bahwa modul yang diterapkan dapat menarik minat siswa untuk mempelajari materi ekosistem. Berdasarkan hasil penelitian dapat disimpulkan bahwa Modul Ekosistem Berbasis Konstruktivisme yang diterapkan efektif digunakan sebagai bahan ajar di SMP YPE Semarang. .